2012
DOI: 10.6026/97320630008175
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis and structure determination of alkaline protease from Aspergillus flavus

Abstract: Proteases are one of the highest value commercial enzymes as they have broad applications in food, pharmaceutical, detergent, and dairy industries and serve as vital tools in determination of structure of proteins and polypeptides. Multiple application of these enzymes stimulated interest to discover them with novel properties and considerable advancement of basic research into these enzymes. A broad understanding of the active site of the enzyme and of the mechanism of its inactivation is essential for deline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In addition to Aspergillus , the bacterial genus Bacillus is widely used for fermenting soybean meal. Bacillus is an ideal industrial microorganism because of its high growth rate and strong capacity to produce extracellular enzymes [10]. Bacillus subtilis yields compounds exhibiting various biological functions, and foods fermented by Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Aspergillus , the bacterial genus Bacillus is widely used for fermenting soybean meal. Bacillus is an ideal industrial microorganism because of its high growth rate and strong capacity to produce extracellular enzymes [10]. Bacillus subtilis yields compounds exhibiting various biological functions, and foods fermented by Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Proteases are hydrolytic enzymes that degrade protein into polypeptides, dipeptides and then to amino acids [1]. In particular, bacterial alkaline proteases play an important role in the industrial biotechnological processes and they are one of the highest value commercial enzymes as they have broad applications in food, pharmaceutical, detergent, and dairy industries [2]. Of them, Bacillus species are considered the most efficient for such purpose as they produce large quantities of the enzyme [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D model for the disulfide reductase showed least homology and only 14% query coverage and 21% sequence identity with the template c3iraA. The PROCHECK report which describes the stereo‐chemical quality for 3D structures revealed that Phyre2‐generated 3D protein structures of template displayed comparable structural homology with the reference proteins with well resolved crystallographic PDB structures as has also been displayed by SWISS‐MODEL, ProSA .…”
Section: Resultsmentioning
confidence: 80%